Performance Study of Modified Savonius Water Turbine with Two Deflector Plates - Golecha Kailash; T. I. Eldho; S. V. Prabhu (International Journal of Rotating Machinery)
Savonius rotor is a vertical axis rotor with simple in design and easy to fabricate at lower cost. The rotation of the rotor is due to the drag difference between the advancing blade and returning blade. Net driving force can be increased by reducing the reverse force on the returning blade or increasing the positive force on the advancing blade. Former can be realized by providing a flow obstacle to the returning blade and latter can be realized by concentrating the flow towards the advancing blade. The objective of the present work is to identify the optimal position of the deflector plate (on advancing blade side) placed upstream to the flow which would result in increase in power generated by the rotor. Tests are conducted to identify the optimum position of the deflector plate on the advancing blade side in the presence of a deflector plate on the returning blade side at its optimum position. Results suggest that two deflector plates placed at their optimal positions upstream to the flow increase the coefficient of power to 0.35. This is significantly higher than the coefficient of power of 0.14 observed for the rotor without deflector plates.